Does affective organizational commitment and experience of meaning at work predict risk of disability pensioning? An analysis of register‐based outcomes using pooled data on 40, 554 observations in four occupational groups. Issue 6 (11th March 2014) - Clausen, Thomas; Burr, Hermann; Borg, Vilhelm
Abstract Background The aim of this study is to investigate whether experience of meaning at work (MAW) and affective organizational commitment (AOC) predict risk of disability pensioning in four occupational groups. Methods Survey data from 40, 554 individuals were fitted to a national register (DREAM) containing information on payments of disability pension. Using multi‐adjusted Cox‐regression, observations were followed in the DREAM‐register to assess risk of disability pensioning. Results Low levels of MAW significantly increased risk of disability pensioning during follow‐up referencing high levels of MAW. Respondents with medium levels of AOC had a significantly reduced risk of disability pensioning, when compared to respondents with high levels of AOC. Furthermore, results indicate an interaction effect between AOC and MAW in predicting risk of disability pension. Conclusions AOC and MAW are significantly associated with risk of disability pensioning. Promoting MAW and managing AOC in contemporary workplaces may contribute towards reducing risk of disability pensioning. Am. J. Ind. Med. 57:709–717, 2014. © 2014 Wiley Periodicals, Inc.